P PELATIHAN TEKNOLOGI PEMBUATAN SABUN PADAT TRANSPARAN DARI MINYAK KELAPA DI DESA ARISAN JAYA KECAMATAN PEMULUTAN BARAT (Ikatan Dosen Menulis, 2023)
Arisan Jaya Village has many local plant commodities that have not been fully utilized, such as coconuts which are scattered in residential areas. Coconut plants are allowed to grow without any care and utilization is only limited to the flesh of the fruit for making coconut milk. Practically owned coconut trees do not contribute to family income. Coconut fruit has the potential to be developed in the context of diversifying agricultural products. Coconut meat can be processed into cooking oil. The resulting cooking oil can be used as raw material for making bath soap that is safe, healthy and can cleanse the body of dirt. Making bath soap from oil can be done using a technology that is easy to understand and implement, so it is hoped that it can be done by a group of women farmers in Arisan Jaya Village.